Electro-thermal therapy: Microsecond duration pulsed electric field tissue ablation with dynamic temperature control algorithms. (June 2020) - Sano, Michael B.; Petrella, Ross A.; Kaufman, Jacob D.; Fesmire, Christopher C.; Xing, Lei; Gerber, David; Fogle, Callie A.
Abstract: Electro-thermal therapy (ETT) is a new cancer treatment modality which combines the use of high voltage pulsed electric fields, dynamic energy delivery rates, and closed loop thermal control algorithms to rapidly and reproducibly create focal ablations. This study examines the ablative potential and profile of pulsed electric field treatments delivered in conjunction with precise temperature control algorithms. An ex vivo perfused liver model was utilized to demonstrate the capability of 5000 V 2 μs duration bipolar electrical pulses and dynamic temperature control algorithms to produce ablations. Using a three applicator array, 4 cm ablation zones were created in under 27 min. In this configuration, the algorithms were able to rapidly achieve and maintain temperatures of 80 °C at the tissue-electrode interface. A simplified single applicator and grounding pad approach was used to correlate the measured ablation zones to electric field isocontours in order to determine lethal electric field thresholds of 708 V/cm and 867 V/cm for 45 °C and 60 °C treatments, respectively. These results establish ETT as a viable method for hepatic tumor treatment with ablation profiles equivalent to other energy based techniques. The single applicator and multi-applicator approaches demonstrated may enable the treatment of complex tumor geometries. The flexibility of ETT temperature control yields a malleable intervention which gives clinicians robust control over the ablation modality, treatment time, and safety profile.